2014
DOI: 10.1002/hipo.22247
|View full text |Cite
|
Sign up to set email alerts
|

Galvanic vestibular stimulation impairs cell proliferation and neurogenesis in the rat hippocampus but not spatial memory

Abstract: Galvanic vestibular stimulation (GVS) is a method of activating the peripheral vestibular system using direct current that is widely employed in clinical neurological testing. Since movement is recognized to stimulate hippocampal neurogenesis and movement is impossible without activation of the vestibular system, we speculated that activating the vestibular system in rats while minimizing movement, by delivering GVS under anesthesia, would affect hippocampal cell proliferation and neurogenesis, and spatial mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…Smith et al and Zheng et al reported that modulation of memory, but not spatial memory, occurs with vestibular lesions and can be influenced by galvanic vestibular stimulation ( 72 , 73 ). These findings may lead to additional treatment strategies that may accelerate or maximize recovery after repairing a no-iOCD or SCD.…”
Section: Discussionmentioning
confidence: 99%
“…Smith et al and Zheng et al reported that modulation of memory, but not spatial memory, occurs with vestibular lesions and can be influenced by galvanic vestibular stimulation ( 72 , 73 ). These findings may lead to additional treatment strategies that may accelerate or maximize recovery after repairing a no-iOCD or SCD.…”
Section: Discussionmentioning
confidence: 99%
“…The 10 min duration of stimulation used for the c‐Fos study was initially based on previous studies of the effects of galvanic vestibular stimulation on cell proliferation in the hippocampus (Zheng et al. ), as well as pilot data. It was assumed that briefer stimulation may not be sufficient to alter c‐Fos expression in the striatum.…”
Section: Discussionmentioning
confidence: 99%
“…This was done using a Dino‐Lite microscopic video camera focused on the rat's eye (Zheng et al. ), images from which were displayed on a PC. For each rat the threshold for nystagmus was defined as the lowest current at which eye movement was visible.…”
Section: Methodsmentioning
confidence: 99%
“…A stainless-steel bipolar electrode (MS303/1-B/SPC, Plastics One Inc.), insulated except at the tip, was placed into the round window as the stimulating electrode. It was secured in place using dental cement once the location of the electrode placement was confirmed via visualisation of vestibular nystagmus in response to stimulation, which was considered evidence that the peripheral vestibular system was being adequately activated [ 12 , 39 ] ( Fig 1C ). The surgical site was then sutured closed.…”
Section: Methodsmentioning
confidence: 99%
“…The surgical site was then sutured closed. Eye movements were recorded using a Dino-Lite microscopic video camera focused on the rat’s eye [ 12 , 39 ], images from which were displayed on a PC monitor. The threshold for nystagmus was defined as the lowest current at which eye movement was visible ( Fig 2 ).…”
Section: Methodsmentioning
confidence: 99%